Impact of transient temperature on the Elderly's physiology and psychology during getting-up process in winter - Zhai, Yingxian; Li, Ziqiao; Qiu, Xiangwei; Zhu, Lu; Lei, Yu; Dai, Longkang; Xie, Xin; Sekhar, Chandra; Liu, Meng (Building and environment, 2024)
The getting-up process in winter was the transition with temperature-dropping and clothes-dressing, which has not been explored in existing research. Due to the decreased thermophysiological adaptability and thermal psychology of the elderly, they may experience sudden changes in thermophysiology and have weak awareness to form appropriate protection. To evaluate the impact of transient temperature on the physiology and psychology of the elderly during getting-up process in winter, thirty elderly subjects aged over 60 years and five younger subjects were recruited for field monitoring at a nursing home in Chongqing. Heart rate and blood pressure were monitored by a physiological wristband, while core and skin temperature were measured by attached sensors. Variability indices were proposed to classify individual differences. Results showed that the temperature difference between the cover and bedroom was 2.4–24.0 °C, and the clothes resistance in elderly increased by 0.70 clo during getting-up process. 25% of the elderly suffered from tachycardia, while the younger did not. Obese elderly exhibited a higher likelihood of experiencing tachycardia when exposed to temperature differences exceeding 15.0 °C. The variabilities in the heart rate and blood pressure in elderly were 70% and 10% larger than in younger, respectively. The average skin temperature of the elderly dropped by 0.7 °C, and their overall thermal sensations decreased by 0.3 scales. The variability of skin temperature and thermal sensation in the elderly were not significantly influenced by surrounding temperature differences or individual differences. This study can provide a reference for research on the health of the elderly in transient environment. •Getting-up was temperature-dropping (2–24 °C) and clothes-dressing (0.7clo) transition.•Proposing variability indexes to solve and classify difference of elderly and youth.•25% of elderly had tachycardia especially with obese, while youth did not suffer.•Variability of heart rate and blood pressure in elderly were all larger than youth.•Skin temperature and thermal sensation in elderly were not significantly influenced.